Gotta buy 'em all? Online shopping cart abandonment among new and existing customers. (8th February 2022) - Rausch, Theresa Maria; Brand, Benedikt M.
For e-retailers, shopping cart abandonment rates are essential measures of their success within the e-market. Extant behavioural literature determined factors triggering cart abandonment, whereas another stream of literature explored customers' online purchase behaviour with clickstream data drawing on different segmentations such as mobile versus desktop shoppers. Nevertheless, research still lacks an understanding of cart abandonment with unbiased user generated behaviour. This study fills a research gap by determining factors resulting in cart abandonment based on clickstream data. Since particularly new and existing customers need to be addressed differently, the study identifies drivers for both. The findings indicate that mobile shoppers exhibit a higher likelihood of abandoning their cart, which even intensifies for new customers. For existing customers, the odds of completing the purchase decreases with every additional item in the customers' cart and new customers are rather likely to abandon the cart with an increasing number of cart page impressions.